A Case Study on Management of Shwitra Through Ayurveda (International Journal of Ayurveda and Pharma Research, 2024)
Introduction: Melanocyte degeneration has a connection to vitiligo, an acquired macular depigmentation disorder. It is thought to be brought on by cells' autoimmune destruction of melanocytes. Frequently symmetrical, generalized vitiligo affects the hands, wrists, feet, knees, neck, as well as the skin around bodily orifices. According to Ayurveda all the skin diseases are categorized under the Kushtha Roga. In the classics Shwitra is mentioned under Kushtha Roga Chikitsa. Methodology: The 10-year-old male child, complaint of white discolored spots on his neck and left clavicle region; Shamana Chikitsa was used to cure the condition satisfactorily. Result: Patient showed encouraging result after Shamana Chikitsa, where subjective criteria evaluated using scoring method and objective criteria evaluated using VASI scoring method. Discussion: Patient was treated with Shamana Aushadhis, where white discolored patches turned to pinkish, and after that the patches turned into normal skin color. Subject was observed with 95% improvement in subjective criteria and VASI scoring improved from 0.25 to 0.10. Hence, the present case study highlights the importance of efficacy of Ayurvedic treatment in Shwitra, as mentioned in classics. Conclusion: Ayurvedic medicine's effectiveness in curing Shwitra was confirmed by the current case study.